2019
DOI: 10.1186/s12889-019-6981-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis and its prevention: knowledge, attitude and practice of urban community in Selangor, Malaysia

Abstract: Background Leptospirosis is still endemic in Malaysia and has been prevalent in Selangor where cases have been underreported. Primarily, this was due to lack of awareness in the urban community in this region. This study determined the knowledge, attitude and preventive practice (KAP) of leptospirosis, and identified the significant predictors influencing KAP among urban community in Hulu Langat, Selangor. Methods This cross-sectional study was conducted from 2015 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
0
23
1
1
Order By: Relevance
“…Very few dairy farmers had knew about transmission of leptospirosis through drinking contaminated water, infected animal urine and contaminated soil & mud (14.44 per cent), and abrasions or cuts in skin, intact skin after prolonged immersion in contaminated water and infected bulls or AI (11.67 per cent). A contrary finding was observed byAbdullah et al (2019) and indicated that majority of respondents (71.4 per cent) thought modes of transmission of leptospirosis were through contaminated food and drinks. Very less per cent of dairy farmers had knowledge about symptoms of animal & human suffering from leptospirosis.…”
mentioning
confidence: 57%
“…Very few dairy farmers had knew about transmission of leptospirosis through drinking contaminated water, infected animal urine and contaminated soil & mud (14.44 per cent), and abrasions or cuts in skin, intact skin after prolonged immersion in contaminated water and infected bulls or AI (11.67 per cent). A contrary finding was observed byAbdullah et al (2019) and indicated that majority of respondents (71.4 per cent) thought modes of transmission of leptospirosis were through contaminated food and drinks. Very less per cent of dairy farmers had knowledge about symptoms of animal & human suffering from leptospirosis.…”
mentioning
confidence: 57%
“…Low perceived susceptibility towards leptospirosis infection may also be due to the poor knowledge about the disease. In a study of rural and urban respondents in Selangor, 57–80.3% had poor knowledge about leptospirosis and its prevention [ 7 , 8 ]. It may also be influenced by the belief towards the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the government efforts undertaken during the past several decades to increase the awareness regarding zoonotic diseases in the population, public understanding of this disease does not appear to have improved [ 6 ]. Previous studies in Malaysia found low to average knowledge, attitude and practice scores on leptospirosis [ 7 , 8 , 9 , 10 , 11 , 12 ]. Misconception about the disease is also widespread [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as reemerging zoonosis in the country, with favorite weather conditions of high humidity and warm temperature allow for the long survival of the pathogens in the environment. Moreover, the disease is still endemic in Malaysia (21,22) as with the entire South East Asia sub-region, with highest prevalence in most states of Peninsular Malaysia with Kelantan, Perak, Selangor and Pahang had the highest rate (23). Unfortunately, the Malaysian data regarding the clinical epidemiology and factors associated with leptospirosis mortality is lacking despite the endemicity of the disease in the country and the expected increased burden of the disease in the future (22) and the disease is underestimated due to its underreporting and misdiagnosis (24).…”
Section: Introductionmentioning
confidence: 99%